(untitled) (Revista de Ciências Agroveterinárias, 2020)
Although bud fruitfulness is important to yield and depends on the most appropriate pruning method, no such information is available for the Northern Highlands of Santa Catarina in Brazil. Therefore, this study proposes to evaluate the bud fruitfulness of American and hybrid grape varieties cultivated in this region. This experiment was conducted in a commercial vineyard located in Pedras Brancas, in the municipality of Canoinhas, Santa Catarina, during the 2018 and 2019 vintages. The study included plants of the following varieties: Ives Noir, White Niagara, Goethe, and Grano d´Oro. Twenty canes from the year of each treatment were collected during the endodormancy phase, and each cane segment containing one bud was arranged in Styrofoam trays with hydrated phenolic foam. The trays were placed in a greenhouse where temperature and humidity were kept under control. The buds were classified as fruitful or unfruitful based on the presence or absence of inflorescence. According to the data in this study, the Goethe, White Niagara, Ives Noir, and Grano D’Oro varieties presented good adaptability as they had high bud fruitfulness, especially the buds in the middle and apical sections of the canes. Thus, mixed pruning of these varieties is recommended to obtain better yields under the conditions of the Northern Highlands of Santa Catarina.